Separation of 90Sr from nuclear waste by crystalline complex phosphates of Ce(IV) and Zr(IV). Issue 2 (April 2018) - Bevara, Samatha; Giri, Prema; Patwe, Sadeque. Jahedkhan; Achary, S. Nagabhusan; Mishra, Raman K.; Kumar, Amar; Sinha, Anil K.; Kaushik, Chetan P.; Tyagi, Avesh Kumar
Graphical abstract: Highlights: Efficient separation of Sr 2+ by K2 Ce(PO4 )2 and K2 Zr(PO4 )2 is reported. Maximum values of Kd (∼30, 000) is observed for K2 Zr(PO4 )2 in neutral condition. Process to transform these materials to immobilize Sr 2+ is suggested. Relation between crystal structure and ion exchange properties are discussed. This study will guide in designing new ion exchange from crystallographic concepts. Abstract: Large amounts of radioactive Sr produced in nuclear reactor need to be separated for alternate use or safe disposal. Herein effective separation of radioactive Sr 2+ by crystalline complex phosphates, namely a tunnel structured K2 Ce(PO4 )2 (KCP) and a layer structured K2 Zr(PO4 )2 (KZP) is reported. These phosphates were prepared by high temperature solid state reaction method and characterized by X-ray diffraction using synchrotron X-ray sources. Ion exchange properties of these materials have been evaluated by using solutions of radioactive 85 Sr. Both the materials show quantitative separation of Sr 2+ but at different pH. Distribution constants (Kd ) show increasing trend with increasing pH and show maximum values ∼ 8000 at pH 14 for KCP and ∼ 30, 000 in neutral medium for KZP. The ion exchange capacities (qe ) increase with increasing Sr 2+ ions concentration and the typical values of qe are ∼ 521 μmol/g for KCP and ∼ 603 μmol/g for KZP. Correlation of structure and ion exchange properties indicated that the layered structure of KZP is the origin for its large Kd . The studies on kinetics and exchange isotherms of both KCP and KZP suggest for pseudo-second order favorable chemisorptions processes. From ex situ high temperature reactions, it is proposed that these lattices can be converted to stable apatite or NZP type matrices with the separated Sr 2+ ions from the nuclear waste.